2020
DOI: 10.1140/epjc/s10052-020-8249-3
|View full text |Cite
|
Sign up to set email alerts
|

Black hole evaporation in Hořava–Lifshitz gravity

Abstract: Hořava–Lifshitz (HL) gravity was formulated in hope of solving the non-renormalization problem in Einstein gravity and the ghost problem in higher derivative gravity theories by violating Lorentz invariance. In this work we consider the spherically symmetric neutral AdS black hole evaporation process in HL gravity in various spacetime dimensions d, and with detailed balance violation parameter $$0\leqslant \epsilon ^2\leqslant 1$$ 0 ⩽ … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(41 citation statements)
references
References 55 publications
(65 reference statements)
2
39
0
Order By: Relevance
“…Also, in the cases D = 4, 5 there always have remnants, while in the cases D 6 that all the black holes will evaporate in a finite time. This phenomenon is quite similar to the Hořava-Lifshitz case [23], which also has the dimensional dependent evaporation behavior.…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…Also, in the cases D = 4, 5 there always have remnants, while in the cases D 6 that all the black holes will evaporate in a finite time. This phenomenon is quite similar to the Hořava-Lifshitz case [23], which also has the dimensional dependent evaporation behavior.…”
Section: Discussionsupporting
confidence: 72%
“…If we obtain the impact factor b c , we can get the Hawking emission rate in D-dimensional spacetime according to Stefan-Boltzmann law, yields [10,21,23,64,65]…”
Section: Black Hole Evaporation In Dmentioning
confidence: 99%
See 1 more Smart Citation
“…The motivation behind such a geometrically extended gravity is to address the late time cosmic phenomena issue. Xu et al [22] also suggested the Weyl type f (Q, T ) gravity and its cosmological implications. Zia et al [23] have obtained the cosmological model in f (Q, T ) gravity applying the energy conservation equation.…”
Section: Introductionmentioning
confidence: 99%
“…After that, Yixin et al [33,34] introduced a symmetric teleparallel gravity extension based on the coupling between non-metricity Q and the trace of the energy-momentum tensor T , i.e., considering an arbitrary function f (Q, T ) in the gravitational action. Using some functional forms of f (Q, T ), some works in this modified gravity look at cosmological models and rapid expansion of the universe.…”
Section: Introductionmentioning
confidence: 99%